2018
DOI: 10.1007/s00109-018-1719-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DJ-1 on the neuroprotection of astrocytes subjected to cerebral ischemia/reperfusion injury

Abstract: Astrocytes are involved in neuroprotection, and DJ-1 is an important antioxidant protein that is abundantly expressed in reactive astrocytes. However, the role of DJ-1 in astrocytes’ neuroprotection in cerebral ischemia/reperfusion injury and its potential mechanism is unclear. Thus, to explore effects and mechanisms of DJ-1 on the neuroprotection of astrocytes, we used primary co-cultures of neurons and astrocytes under oxygen and glucose deprivation/reoxygenation in vitro and transient middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 49 publications
(73 reference statements)
1
37
0
1
Order By: Relevance
“…Previously, we reported that astroglial DJ-1 plays a critical role in neuroprotection in ischemic injury [20]. These findings led us to further study the protective mechanism of astroglial DJ-1.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Previously, we reported that astroglial DJ-1 plays a critical role in neuroprotection in ischemic injury [20]. These findings led us to further study the protective mechanism of astroglial DJ-1.…”
Section: Introductionmentioning
confidence: 85%
“…DJ-1 siRNA was obtained and used as described in our previous studies [20]. AAV was purchased from Neuron Biotech (Shanghai, China).…”
Section: Treatment With Dj-1 Sirna or Dj-1 Adeno-associated Virus (Aav)mentioning
confidence: 99%
See 3 more Smart Citations